2020
DOI: 10.1515/reveh-2020-0062
|View full text |Cite
|
Sign up to set email alerts
|

The use of indoor plant as an alternative strategy to improve indoor air quality in Indonesia

Abstract: Indoor air pollution marked with decreased air quality below the set standard. The quality of indoor air is determined by ambient air quality as well as by a harmful substance resulting from the household activity. Indoor air pollution may cause several problems such as sick building syndrome, chronic obstructive pulmonary disease (COPD), asthma, lung cancer, and is responsible for nearly two million death in developing countries. One of the interesting research topics to overcome the indoor air pollution prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 40 publications
0
12
0
2
Order By: Relevance
“…Plants in indoor environments promote healthy and comfortable living by absorbing pollutants [70]. Plant evapotranspiration helps to decrease the temperature in the surrounding environment.…”
Section: Air Cleaning Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plants in indoor environments promote healthy and comfortable living by absorbing pollutants [70]. Plant evapotranspiration helps to decrease the temperature in the surrounding environment.…”
Section: Air Cleaning Plantsmentioning
confidence: 99%
“…This helps to maintain a person's mental health by reducing the sick building syndrome effect [71]. Plants also have potential to purify indoor air through a phytoremediation process in which plants absorb and catabolize various toxic substances [70]. Using indoor plants to purify air may be a cost-effective and energy-efficient option to promote healthy buildings.…”
Section: Air Cleaning Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies for applying this pattern in the workplace can be identified in implementation of indoor plants illustrated in landscaping of trees and bushes, potted or hanged plants, green walls, etc. Beside adding an aesthetic value to the space, plants purify air from pollutants resulting from carpets and new furniture which improves indoor air quality [16], additionally it absorbs ambient noise and reduce acoustical distractions [17].…”
Section: Visual Connection With Nature [P1]mentioning
confidence: 99%
“…Han and Ruan (2020) conducted a systematic review and found that indoor plants have the potential to improve the air quality, followed by a decrease in temperature and an increase in humidity. In contrast, Susanto et al (2021) suggested that indoor plants can be used as an alternative way to reduce indoor air pollution.…”
Section: Introductionmentioning
confidence: 99%